Evaluation of the effects of overdose Acetaminophen toxicity in rats: Ozone, which can be preferred as a complementary therapy - Kaya, Emre; Yilmaz, Seval; Aksu, Feyza; Kavakli, Ahmet (Univ Zulia, Facultad Ciencias Veterinarias, 2024)
This study aims to investigate the effects of ozone therapy used in traditional and complementary medicine on possible toxicity caused by acetaminophen (APAP). There was no intervention in the first group (control). The second group received 150 mu gkg (-1) day, ip for three weeks of ozone, 2 gkg (-1) of APAP in a single dose orally to the third group and APAP + Ozone to the fourth group. APAP was administered on day 21 of ozone application. Malondialdehyde (MDA) levels, reduced glutathione (GSH) levels, and antioxidant enzyme activities were measured to evaluate their contribution to the pathogenesis of blood tissue toxicity. Compared with the control group, the group receiving APAP showed elevated levels of MDA ( P =0.009) and decreased levels of GSH ( P <0.001), as well as reduction of CAT ( P <0.001), GSH-Px ( P < 0.001) and SOD. ( P < 0.001) enzyme activities. However, in the group treated with ozone and APAP, the levels of MDA and GSH, as well as the activities of antioxidant enzymes, were similar to those of the control group, indicating a protective effect of ozone against induced oxidative stress. by APAP. In conclusion, the study results showed that APAP caused oxidative stress in blood tissue. The present study demonstrated that ozone had potential protective effects against APAP-induced toxicity through several mechanisms in different cellular processes. This may be related to the cytoprotective and antioxidant properties of ozone. Ozone may provide a chemical basis for some health benefits against toxicities. Ozone may protect against APAP-induced oxidative damage. As a result, it was concluded that ozone may be a natural and effective antioxidant that can be used to reduce the toxicity caused by APAP.
Evaluación de los efectos de la toxicidad por sobredosis de paracetamol en ratas: el ozono, que puede preferirse como terapia complementaria
Keywords: Acetaminophen; antioxidant; ozone; oxidative stress; toxicity